MODE OF OPERANDI OF SUBSIDIZED SOLAR OIL FUEL STORAGE (CASE STUDY ON HIGHWAY KM 8 TANDUN WEST VILLAGE, TANDUN DISTRICT, ROKAN HULU DISTRICT) - Aldo, Ferdy marealdo; Askarial (Sisi Lain Realita, 2023)
This research aims to find out the modus operandi of hoarding subsidized diesel fuel that occurs on Jalan Raya Km 8, West Tandun Village, Tandun District, Rokan Hulu Regency. This research examines the modus operandi of storing subsidized diesel fuel on Jalan Raya Km 8, West Tandun Village, Tandun District, Rokan Hulu Regency. The modus operandi includes techniques used by perpetrators to illegally accumulate fuel for financial gain. The research method applied was qualitative, with a field observation approach and in-depth interviews with the perpetrators and the local community. The research results show that perpetrators utilize unofficial distribution networks and manipulate subsidy quotas to hoard fuel, which causes shortages for the community. The conclusion of this research is that hoarding practices have a significant negative impact on the availability of fuel for the community. Therefore, it is necessary to increase supervision and stricter law enforcement in the distribution of subsidized fuel to protect public interests and ensure fair access to energy resources. Apart from that, outreach regarding subsidy regulations needs to be carried out to increase public awareness of this illegal practice.